Faktor-Faktor yang berhubungan dengan Kecelakaan Kerja Petani Karet Suku Anak Dalam (SAD) - Asparian, Asparian; Oktafia, Dinda; Aswin, Budi; Fatmawati, Tina Yuli (Jurnal Akademika Baiturrahim Jambi, 2024)
Rubber farmers of the Suku Anak Dalam (SAD) are among the informal sector workers at risk of work accidents. This is due to the characteristics of the SAD community, which predispose them to such accidents. The aim of this study is to identify factors associated with work accidents among SAD rubber farmers in Bukit Suban Village, Sarolangun Regency. This research adopts a quantitative approach with a cross-sectional design. The study population comprises heads of households engaged in rubber farming in Bukit Suban Village, Sarolangun Regency, totaling 81 individuals. Data analysis employs the chi-square statistical test. The research findings indicate a prevalence of work accidents among rubber farmers at 55.6%. The results demonstrate significant relationships between age, years of service, safe behavior, use of personal protective equipment (PPE), and soil conditions with work accidents (p-value <0.05), while occupational safety training (K3) and equipment location show no correlation with work accidents among SAD rubber farmers. Dominant factors contributing to work accidents include age, soil conditions, and safe behavior. Multivariate analysis reveals that age is the most dominant factor associated with work accidents (p-value 0.000, PR=17.076, 95% CI = 4.503-64.757). It is recommended that local government agencies provide support in enhancing work safety and offer assistance in the form of PPE to improve understanding and knowledge of work safety, thereby reducing work accidents among SAD rubber farmers